A Comprehensive Research Study Literature Review of EPIC© in Terms of Enabling Healthcare Agility: A Report Card - Ralph J. Johnson (Journal of Medical Informatics and Decision Making, 2021)
Background As healthcare markets have become more dynamic and turbulent, healthcare organizations have evolved by becoming increasingly “Smart-Agile” in their business practices. Smart-Agility definition-ally ensures success due to its inherent ability to rapidly detect and react appropriately to varied and evolving unclear, complex, and seemingly tumultuous situations and produce high-quality, low-cost goods and services with high customer satisfaction. Thus, there is a vital need for Smart-Agile healthcare IT systems for collection, analyses, and reporting of substantial quantities of healthcare data to inform patient treatment and organizational decisions. EPIC® and its meaningful-use components appear increasingly popular, capturing a majority portion of the healthcare Electronic Healthcare Records (EHR) IT market (> 30%).Yet, there are few, if any, studies reporting on EPIC in terms of Smart-Agility. Aim The intent of this article is to report a systematic review of scientific literature regarding EPIC’s healthcare IT systems meaningful-use features cross-compared with Smart-Agility aspects to produce a positive vs. negative report card—and whether its features are critical vs. non-critical in terms of Smart-Agility. Method Findings reported herein derive from a grounded, iterative review of open-source, peer-reviewed scientific literature following PRISMA. Findings Report card results were mixed. EPIC clearly succeeds and excels (better than average) on Smart-Agile healthcare IT system core aspects that are the most central, critical and valuable in terms of informing healthcare organizations’ decisions and their patients’ care (6 out of 7; B+, -A), specifically: Standardized Data Collection / Connectivity, Real-Time Data Warehousing/Outcome Measures, Enhanced Patient Safety, Patient Tracking and Follow-up (Continuity of Care), Patient Involvement, and Potential Use in Medical Education. The only critical core criterion it failed on was End-User Satisfaction, and some of that appears to dissipate with new users’ software familiarity. Conclusion EPIC provides a solid and relatively inexpensive foundation with great potential for enabling Smart Agility in healthcare organizations with its high-quality collection and management of vast amounts of inter-connected raw data, auto-analysis, and fast report generation. But it does so with hidden costs and inefficiencies. Avenues of further inquiry are suggested.
Keywords: Agility